Relative Importance of Ecological, Evolutionary and Anthropogenic Pressures on Extinction Risk in Chinese Angiosperm Genera - Yu, Haibin; Sui, Xinghua; Sun, Miao; Yin, Xue; Deane, David C. (Frontiers in Ecology and Evolution, 2022)
China has many threatened plant species, which are exposed to environmental degradation and other anthropogenic pressures. We assessed support for potential extinction pathways in Chinese angiosperm genera and quantified possible threats to phylogenetic diversity. We compiled a database and phylogeny for 27,409 Chinese angiosperm species in 2,453 genera. For each genus, we used IUCN Red List classifications to quantify extinction risk and calculated predictors corresponding to their ecological, evolutionary characteristics and exposure to human pressures. We first tested for phylogenetic clustering in extinction risk among genera, and then tested support for direct and indirect causal pathways involving our predictors using piecewise structural equation models. Finally, we quantified the potential loss of phylogenetic diversity under different extinction scenarios. We found that extinction risk is non-randomly distributed among Chinese angiosperm genera, with the proportion of threatened species higher in range-limited and species-rich taxa. Habitat loss had a significant positive effect on threatened species richness. Phylogenetic diversity loss under scenarios: the decreasing habitat loss and relative extinction rate were high. Thus, genera would suffer high extinction risk if species in these genera occupy similar niches and overlapping ranges. While diversification or speciation via niche divergence might increase range-limited species vulnerable to stochastic extinction, this could reduce extinction risk of the whole clade by expanding its range and climatic niche tolerance. Endemic genera with higher extinction rates, less climatic niche divergence, and lower range segregation are especially vulnerable to anthropogenic disturbances.